Students' Perceptions of the Importance of English in the Workplace - Devi Andreawati; Yeni Rahmawati; Sunarti (Universitas Islam Negeri Palopo, 2026)
English proficiency is vital for workplace communication in globalized, technology-driven environments, yet few studies examine vocational high school students' perceptions, which differ from those of general secondary education students due to industry-specific needs. This study investigates eleventh-grade students' perceptions of English for workplace readiness and identifies essential skills. Using a mixed-methods design, quantitative data from a 22-item Likert-scale questionnaire (n=180) and qualitative data from semi-structured interviews (n=20) were analyzed via descriptive statistics and thematic analysis. Findings reveal strong positive perceptions of English for career development and employability, with speaking as the most valued skill (mean = 3.38). However, there is a mismatch between perceptions and workplace demands, as students prioritize speaking over reading/writing. Qualitative themes highlight instructional gaps and proactive self-learning. Vocational curricula should integrate practical, industry-aligned activities to enhance readiness.